667 Motorcycle one-wheeling: a fatal venture in Pakistan. (1st September 2016) - Tahir, Muhammed Navid; Akbar, Ali Hammad; Kayani, Ahsan; Ramadhani, Saif Al; Haworth, Narelle; King, Mark; Naseer, Rizwan
Abstract : Background: Motorcycle one-wheeling (MOW) is one of the burgeoning factors in motorcycle crashes in Pakistan. Young One-wheelers (YOW) perform dangerous stunts such as riding motorcycle while laying flat, lifting front-wheel and their backs facing motorcycle handles. Consequently, they put themselves and others at risk. A newspaper reported that over 200 YOW died and around 1, 300 other road users were injured or killed in MOW crashes during 2011–2013. Current research is the first in Pakistan that presents the most recent epidemiology of MOW crashes. Methods: Retrospective analysis was conducted on crash data for last two years collected by Rescue 1122 (an emergency service in Pakistan) from 37 major cities of Province Punjab. Results: Rescue 1122 attended 389 MOW crashes during the study period. Of them, maximum MOW crashes were reported in Kasur ( n = 88), followed by Lahore ( n = 69) and Rawalpindi ( n = 41). In all 351 injuries and 16 fatalities were reported among YOW. Of the 351 injuries, about 70% were critical (head, spinal & fractures). All 16 fatalities were aged between 16 and 25 years. Most (19%) were aged 21 years, followed by 13% amongst aged 18, 19 and 22 years respectively. None of fatalities/injured YOW were wearing helmet. Most MOW crashes were reported on Pakistan Independence Day (14 August) and Chand Rat—a night before Eid, whilst some of them were also reported on normal week-days. Conclusions: Prevalence of MOW crashes across Punjab is alarming, as initially this dangerous venture was only confined to large cities. In addition to major cities, MOW crashes are mostly reported from Kasur, which is a suburban city. Though MOW crashes constitute only 1% of reported crashes, their outcomes are very severe, as all MOW fatalities/injured included youngsters have devastating psycho-social impacts on the society. A serious effort is required on part of all the stakeholders. School road safety education with parents partaking is also very important in this view.